Atherosclerosis Burdens in Diabetes Mellitus: Assessment by PET Imaging - Høilund-Carlsen, Poul F.; Piri, Reza; Madsen, Per Lav; Revheim, Mona-Elisabeth; Werner, Thomas J.; Alavi, Abass; Gerke, Oke; Sturek, Michael (International journal of molecular sciences, 2022)
Arteriosclerosis and its sequelae are the most common cause of death in diabetic patients and one of the reasons why diabetes has entered the top 10 causes of death worldwide, fatalities having doubled since 2000. The literature in the field claims almost unanimously that arteriosclerosis is more frequent or develops more rapidly in diabetic than non-diabetic subjects, and that the disease is caused by arterial inflammation, the control of which should therefore be the goal of therapeutic efforts. These views are mostly based on indirect methodologies, including studies of artery wall thickness or stiffness, or on conventional CT-based imaging used to demonstrate tissue changes occurring late in the disease process. In contrast, imaging with positron emission tomography and computed tomography (PET/CT) applying the tracers 18F-fluorodeoxyglucose (FDG) or 18F-sodium fluoride (NaF) mirrors arterial wall inflammation and microcalcification, respectively, early in the course of the disease, potentially enabling in vivo insight into molecular processes. The present review provides an overview of the literature from the more than 20 and 10 years, respectively, that these two tracers have been used for the study of atherosclerosis, with emphasis on what new information they have provided in relation to diabetes and which questions remain insufficiently elucidated.